Condition of the Wild Boar (Sus scrofa) in the Steppe Ukraine - Volokh, Anatolii; Волох, Анатолий Михайлович; Волох, Анатолій Михайлович (My University, 2008)
Most preferable biotopes for the wild boars are natural planted forests (where more than 70 % of animals were observed) and reed beds (more than 15 % of observations). About 75% (60.0-82.4) of adult females participate in reproduction. In a period of intensive development of steppe populations their fertility is 7.2 - 0.26 juveniles. Broods of 5-7 juveniles (56, 14 %) and 8-9 ones (28.07 %) are the most common. Broods of 10-13 (10.53 %) juveniles or 1-4 (5.26 %) ones are rarer. Nowadays the fertility of the wild sows has reduced. The size of broods decreases in July-October up to 6.3 - 0.19 juveniles (1-10). In November-December when the hunting season is opened, the size of broods is 4.4 - 0.21 (1-8). Later, the number of juveniles in one brood decreases up to 4.3 - 0.35 in January and 3.10 - 0.38 in March. Main causes of the wild boars’ mortality are: work of hydro-electric power stations and melioration systems, severe winters (in 1971/1972, 1984/1985 and 1986/1987) with the air temperatures about (-25)°C, long-term snowfall, ice-cover on the ground and also poaching. The numbers of wolves increased in 1995-2000 and mortality of the wild boars caused by attacks of predators also has increased. Death of the wild boars caused by pasteurellosis and anthrax is known. Among 452 wild boars found dead there were 78.10% animals at the age less 1 year (52.88 % of all investigated ones were younger than 9 months). Other dead wild boars were at the following age: 1 year and 8 months (11.95 %), 2 years and 8 months (6.20 %), 3 years and 8 months (2.43 %), 5 years and 8 months (1.10%) and one wild sow was at the age of 18 years. The wild boar steppe population includes 58.6 % of juveniles (1st year of life), 14.3% of yearlings (2nd year of life), 11.5% of adult males and 15.6% of females. Contact
Keywords: wild boar; area; steppe zone; Ukraine; population; dynamics; structure; biotopes; hunting